What Matters for C4 Transporters: Evolutionary Changes of Phosphoenolpyruvate Transporter for C4 Photosynthesis - Lyu, Ming-Ju Amy; Wang, Yaling; Jiang, Jianjun; Liu, Xinyu; Chen, Genyun; Zhu, Xin-Guang (Frontiers in Plant Science, 2020)
C4 photosynthesis is a complex trait that evolved from its ancestral C3 photosynthesis by recruiting pre-existing genes. These co-opted genes were changed in many aspects compared to their counterparts in C3 species. Most of the evolutionary changes of the C4 shuttle enzymes are well characterized, however, evolutionary changes for the recruited metabolite transporters are less studied. Here we analyzed the evolutionary changes of the shuttle enzyme phosphoenolpyruvate (PEP) transporter (PPT) during its recruitment from C3 to C4 photosynthesis. Our analysis showed that among the two PPT paralogs PPT1 and PPT2, PPT1 was the copy recruited for C4 photosynthesis in multiple C4 lineages. During C4 evolution, PPT1 gained increased transcript abundance, shifted its expression from predominantly in root to in leaf and from bundle sheath cell to mesophyll cell, and gained more rapid and long-lasting responsiveness to light. Modifications occurred in both regulatory and coding regions in C4 PPT1 as compared to C3 PPT1, however, the PEP transporting function of PPT1 remained. We found that PPT1 of a Flaveria C4 species recruited a MEM1 B submodule in the promoter region, which might be related to the increased transcript abundance of PPT1 in C4 mesophyll cells. The case study of PPT further suggested that high transcript abundance in a proper location is of high priority for PPT to support C4 function.